Analytical Axiology of the Political Background in “Vision of Teodros” Ethiopian Historical Theater - Ashebir Sinshaw, Mr. Girmaw (International Journal of Scientific Research and Management (IJSRM), 2018)
This article aims to describe about the analytical axiology of the political background in ye Tewodros raey historical theatre of Ethiopia. The theatre is the most important of the new generation to teach the Emperor Tewodros II challenges and also great visions of new civilized Ethiopia united. The theatre name also in English vision of Tewodros in Amharic are known ye Tewodros raey.  As aspect of axiology have been evaluated the value of vision of Theodros to the audience and the advantages. From the theater an axiology aspect of the political background vision of Theodros that the advantages are to more informative about patriotism, social awareness, concentration, imagination, communication skill, fun, problem solving/conflict resolution, trust, memory, aesthetics appreciation, cooperation/collaboration, empathy and tolerance. These papers have been used document study system as well as have used the qualitative research method to more describe as a theatre reviewing the aspect of axiology philosophical aspects.